Novel Control Strategy of Single Matrix Traction Converter – Variable Switching Frequency - Bednar, Bedrich; Blahnik, Vojtech; Drabek, Pavel; Pittermann, Martin (Elektronika ir Elektrotechnika, 2015)
This paper describes research into a novel control strategy of traction converter for the AC-Trolley Line with the middle frequency transformer (MFT). Attention is paid to the problematics of finding a suitable control algorithm that will provide minimal magnetic saturation. This could be ensured by variable pulse widths, determined according to the actual value of input voltage. Special attention is focused on the single-phase matrix converter topology and the best commutation solution. Two basic methods of controlling the switches in the matrix converter are discussed. The first method requires some knowledge of the converter output current polarity and the second method assumes some knowledge of the input voltage polarity. In addition, the article describes the switching method in uncertain states – when the voltage or current cross zero. Moreover, the paper presents a new modular topology with several separate middle frequency transformers. The proposed algorithm is described and implemented in the laboratory model. DOI: http://dx.doi.org/10.5755/j01.eee.21.5.13318